Human APECED; a Sick Thymus Syndrome? - Arstila, Petteri; Jarva, Hanna (Frontiers in Immunology, 2013)
Loss-of-function mutations in the Autoimmune Regulator (AIRE) gene cause a rare inherited form of autoimmune disease, autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED), also known as autoimmune polyglandular syndrome type 1 (APS-1). The patients suffer from multiple endocrine deficiencies, the most common manifestations being hypoparathyroidism, Addison's disease, hypogonadism and secondary amenorrhea, usually accompanied by typical autoantibodies against the target tissues. Chronic mucocutaneous candidiasis is also a prominent part of the disease. The highest expression of AIRE is found in medullary thymic epithelial cells (mTECs). Murine studies suggest that it promotes ectopic transcription of self antigens in mTECs and is thus important for negative selection. However, failed negative selection alone is not enough to explain key findings in human patients, necessitating the search for alternative or additional pathogenetic mechanisms. A striking feature of the human AIRE-deficient phenotype is that all patients develop high titres of neutralizing autoantibodies against type I interferons, which have been shown to downregulate the expression of interferon-controlled genes. These autoantibodies often precede clinical symptoms and other autoantibodies, suggesting that they are a reflection of the pathogenetic process. Other cytokines are targeted as well, notably those produced by Th17 cells; these autoantibodies have been linked to the defect in anti-candidal defenses. A defect in regulatory T cells has also been reported in several studies and seems to affect already the recent thymic emigrant population. Taken together, these findings in human patients point to a widespread disruption of T cell development and regulation, which is likely to have its origins in an abnormal thymic milieu. The absence of functional AIRE in peripheral lymphoid tissues may also contribute to the pathogenesis of the disease.